C++ for engineers and scientists - Bronson, Gary J. (PWS Pub., 1999)
With C++ gaining a stronghold in the engineering and scientific communities, Bronson's book makes C++ accessible to first level engineering students. Featuring a wealth of practical, engineering-oriented examples and applications, the book teaches the fundamentals of the C++ language with a gradual refinement of programming skills from a procedural to an object orientation.